Metode Penanaman Karakter Religius Siswa di Madrasah Ibtidaiyah - Saifudin; Muhammad Yusuf; Fatmawati Norma Sari (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
The cultivation of character values ​​in schools is not without reason. The dilapidated character of the younger generation is the main problem. Character education is the responsibility of all parties, especially schools, as a vehicle for formal education. It is very important to instill character values ​​in children from an early age. MI Tarbiyatus Shibyan Brangkal Kepohbaru Bojonegoro as a basic education institution has implemented character values, especially religious characters through school programs. This study aims to find out what the values ​​of students' religious character are and how the methods used to instill students' religious character at MI Tarbiyatus Shibyan Brangkal Kepohbaru Bojonegoro. This study uses a type of qualitative research with a descriptive approach that has a model to describe and give meaning to the research results. The subject of the research is the method of inculcating the religious character of students and the values ​​of the religious character of students at MI Tarbiyatus Shibyan Brangkal Kepohbaru Bojonegoro. Data collection techniques using interviews, observation, and documentation. Data analysis uses two or three ways, namely, data presentation and drawing conclusions. And test the validity of the data using data triangulation. The results showed that the method used by the teacher in instilling religious character in the students of MI Tarbiyatus Shibyan Brangkal Kepohbaru Bojonegoro was three methods, namely the method of habituation (routine activities), the method of spontaneity, and the method of exemplary. However, the most effective method is habituation (routine activities). Although the religious character has been planted in students and the value of religious character possessed by students is good, especially the value of politeness, it is still not optimal among the values ​​of the religious character, which are as follows: getting used to doing 3S culture (smiles, greetings, and greetings), and shaking hands while kissing the teacher's hand.